1997
DOI: 10.1080/15216549700202291
|View full text |Cite
|
Sign up to set email alerts
|

Bovine kidney low molecular weight acid phosphatase: FMN‐dependent kinetics

Abstract: A low molecular weight bovine kidney acid phosphatase, electrophoretically homogeneous and with a relative molecular mass of 17.8 kDa, was used in this work. Among the various substrates tested, FMN was found to be the most effective, at pH 7.0. Distinct activation energy values were obtained for p‐nitrophenyl phosphate‐ (45.44 kJ mol‐1) and flavin mononucleotide‐ (28.60 kJ mol‐1) hydrolysis reactions. The FMN hydrolysis was strongly inhibited by Cu2+ and pCMB, but activated by guanosine. Pyridoxal‐phosphate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 9 publications
2
20
0
9
Order By: Relevance
“…Some substrates that are present in the cellular metabolism, or natural substrates, were hydrolyzed at similar rates as that of the synthetic one. The efficient rate of hydrolysis of the natural substrates β-glycerol phosphate and FMN found in this study was also observed for acid phosphatases extracted from Chlamydomonas reinhardtii (Matagne et al, 1976) and from bovine kidney (Granjeiro et al, 1997). Similar enzymatic activities were reported for the cleavage of D-glucose 6-phosphate, D-fructose 6-phosphate and 5´AMP by the acid phosphatase extracted from de algae Enteromorpha linza (Yamamoto, 1972).…”
Section: Cleavage Of Substrates and Phosphatase Inhibitionsupporting
confidence: 69%
See 3 more Smart Citations
“…Some substrates that are present in the cellular metabolism, or natural substrates, were hydrolyzed at similar rates as that of the synthetic one. The efficient rate of hydrolysis of the natural substrates β-glycerol phosphate and FMN found in this study was also observed for acid phosphatases extracted from Chlamydomonas reinhardtii (Matagne et al, 1976) and from bovine kidney (Granjeiro et al, 1997). Similar enzymatic activities were reported for the cleavage of D-glucose 6-phosphate, D-fructose 6-phosphate and 5´AMP by the acid phosphatase extracted from de algae Enteromorpha linza (Yamamoto, 1972).…”
Section: Cleavage Of Substrates and Phosphatase Inhibitionsupporting
confidence: 69%
“…The activation energy obtained in our experiments (37.94 kJ mol ) is similar to those described by Lien & Knutsen (1973) for phosphatases extracted from the green algae C. reinhardtii (44.73 kJ mol -1 ) and for the acid phosphatases from other organisms, for example, bovine kidney (45.44 kJ mol -1 ) (Granjeiro et al, 1997). The activation energy value obtained for the acid phosphatase in this work is also closed to the values reported for other algae enzymes, such as hydrogenase (Schnackenberg et al, 1993) and urate oxidase (Alamillo et al, 1991) …”
Section: Kinetics Studiessupporting
confidence: 69%
See 2 more Smart Citations
“…Acid phosphatases (EC 3.1.3.2), enzymes that catalyze the hydrolysis of a wide range of orthophosphate monoesters, are largely distributed in nature and have been studied in numerous organisms and tissues (Granjeiro et al, 1997;Ferreira et al, 1998aFerreira et al, , 1998bGranjeiro et al, 1999;Fernandes et al, 2003;Jonsson et al, 2007). The enzyme found in mammalian tissues occurs in multiple forms that differ in regard to molecular mass, substrate specificity and sensitivity to inhibitors (Granjeiro et al, 1997).…”
Section: Acid Phosphatase 341 Signaling Featuresmentioning
confidence: 99%